2017
DOI: 10.1080/0886022x.2017.1326384
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydroalcoholic extract of Pistacia vera against gentamicin-induced nephrotoxicity in rats

Abstract: Purpose:Pistacia vera is a plant of the family Anacardiaceae found in Central and West Asia. P. vera nut (Pistachio) possess multiple pharmacological effects such as antimicrobial, anti-hyperlipidemia, antioxidant and anti-inflammatory. This study is designed to evaluate the protective effect of the hydroalcoholic extract of pistachio on gentamicin-induced nephrotoxicity in rats.Methods: Nephrotoxicity was induced in rats by intraperitoneal injection of gentamicin (100 mg/kg/day for 7 days). Hydroalcoholic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Consistent with biochemical assessment, renal histopathological results demonstrate structural changes in renal tissue of CP‐treated rats. We showed that administration of CP at the dose 200 mg/kg causes histopathological lesions in kidney like hemorrhage, tubular degeneration and leukocyte cell infiltration tubular and these findings are in agreement with the previous studies . Inflammation could directly cause renal damage and promote kidney cell death via the production of ROS during inflammatory processes .…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with biochemical assessment, renal histopathological results demonstrate structural changes in renal tissue of CP‐treated rats. We showed that administration of CP at the dose 200 mg/kg causes histopathological lesions in kidney like hemorrhage, tubular degeneration and leukocyte cell infiltration tubular and these findings are in agreement with the previous studies . Inflammation could directly cause renal damage and promote kidney cell death via the production of ROS during inflammatory processes .…”
Section: Discussionsupporting
confidence: 92%
“…Gentamicin-induced nephrotoxicity at the beginning of the development of the pathological process is characterized by the development of oliguric form of renal failure, accompanied by retention azotemia, proteinuria, increased loss of sodium and potassium ions with urine, resulting in hypokalemia (Table 1), which reflects the significant damage and death of proximal tubular cells along with injury of glomeruli, and corresponds to the results of similar experimental studies of other authors [1, 4, 8-12, 17, 18]. According to the obtained results of the morphological examination, histopathological changes, namely the necrosis and degeneration of the proximal tubular epithelial cells in the form of vacuolization and hydropic dystrophy, and glomerular damage ( Figure 2) were revealed for gentamicin nephropathy [3,[8][9][10][11][12]14]. It is known that the most important mechanism of gentamicin nephrotoxicity is the hyperproduction of reactive oxygen species, causing damage to proteins, DNA and peroxidation of lipids, with an alteration of the integrity of cellular membranes and development of morphofunctional disorders [1,17].…”
Section: Discussionsupporting
confidence: 87%
“…It is known that the most important mechanism of gentamicin nephrotoxicity is the hyperproduction of reactive oxygen species, causing damage to proteins, DNA and peroxidation of lipids, with an alteration of the integrity of cellular membranes and development of morphofunctional disorders [1,17]. This fact conditions numerous research on the effectiveness of prevention of the gentamicin nephropathy, using known and new antioxidants [1,2,4,[8][9][10][11][12]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that administration of Cisplatin (CP) or CP + Cerium oxide nanoparticles (CeO2 NPs) in rats increased the water intake and urine volume compared with saline, indicated that the damaged renal tubules could cause the deterioration of capacity of tubular cells to reabsorb water, and subsequent polyuria leading to dehydration (Nemmar et al, 2019). Similarly, the increase of urine volume was one of the nephrotoxicity characteristics in an acute renal failure (ARF) rat model induced by gentamicin in a study about plant extracts for the prevention and attenuation of ARF (Ehsani et al, 2017). These results suggested that the physiological functions of the kidney were damaged, resulting in an imbalance of hydration state after exposure to PM 2.5 .…”
Section: Discussionmentioning
confidence: 93%